The Effects of XIAP Gene Therapy in a Murine Model of Leber’s Hereditary Optic Neuropathy and a Feline Model of Retinal Detachment - Wassmer, Sarah (Université d'Ottawa / University of Ottawa, 2017)
In Canada alone, there were an estimated 800,000 visually impaired people in 2007, costing the federal government an annual amount of $15.8 billion in services, treatments and lost revenue. These costs are estimated to double by the year 2032, as the population ages. The leading causes of visual impairment and blindness is retinal degeneration, characterized by the progressive death of retinal cells. The research presented in this PhD thesis aimed to prevent retinal degeneration by over-expressing the X-linked Inhibitor of Apoptosis (XIAP) in retinal cells using plasmid and adeno-associated viral vectors. The work is divided into four sequential chapters targeted at developing an anti-apoptotic gene therapy strategy to prevent retinal cell death. The first chapter examines XIAP gene therapy in the treatment of Leber’s Hereditary Optic Neuropathy (LHON). In vitro studies using the 661W cone-photoreceptor cell line showed that XIAP over-expression significantly lowers cell death when 661W cells are exposed to a number of apoptotic stimuli. In a mouse model of Leber’s Hereditary Optic Neuropathy (LHON), XIAP expression in retinal ganglion cells (RGCs) protected the ultrastructure of the RGC axons within the optic nerve, in addition to providing evidence of functional protection. The second and third chapters further examine the potential for XIAP gene therapy in the treatment of retinal disease by developing an in vivo model of retinal detachment in cats, followed by evaluating the efficacy of XIAP gene therapy intervention. When XIAP was over-expressed in the photoreceptor cells, there was significant structural protection and trends in preservation of function in this model of degeneration. Finally, the fourth chapter explores an alternate method to viral gene therapy by evaluating the efficacy and toxicity of chitosan microparticles as a protein delivery system to the retina. Results show that chitosan microparticles are mucosal-adhesive and are non-toxic at low concentrations in vitro in 661W cells and in vivo in rats. This thesis work provides strong evidence that XIAP gene therapy is an effective method for preventing retinal degeneration, and works as a broad spectrum gene therapy strategy that can be applied to different forms of retinal degeneration.
Keywords: X-linked Inhibitor of Apoptosis (XIAP); Apoptosis; Retinal Detachment; Retina; Neuroprotection; Microparticles; Adeno-associated Virus (AAV); Leber's Hereditary Optic Neuropathy; Retinal Ganglion Cells; Photoreceptors; Tumor Necrosis Factor; Optical Cohence Tomography; Electroretinography; Cell Death; Subretinal Injection; Intravitreal Injection; Gene Therapy; Immunohistochemistry